Evolution of 'pollinator'- attracting signals in fungi. - Schiestl, Florian P; Steinebrunner, Fabrizio; Schulz, Claudia; Von Reuss, Stephan; Francke, Wittko; Weymuth, Christophe; Leuchtmann, Adrian (My University, 2006)
Fungi produce a plethora of secondary metabolites yet their biological significance is often little understood. Some compounds show well-known antibiotic properties, others may serve as volatile signals for the attraction of insects that act as vectors of spores or gametes. Our investigations in an outcrossing, self-incompatible fungus show that a fungus-produced volatile compound with fungitoxic activities is also responsible for the attraction of specific insects that transfer gametes. We argue that insect attraction using this compound is likely to have evolved from its primary function of defence--as has been suggested for floral scent in the angiosperms. We, thus, propose that similar yet convergent evolutionary pathways have lead to interspecific communication signals in both fungi and plants.
Keywords: volatiles; scent; fly pollination; epichloë